Skunk rabies in texas: a retrospective look (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Skunk rabies in Texas, USA is ubiquitous, with the majority of the state within the range of the South-Central skunk rabies distribution. Statewide public health surveillance indicates a cyclic trend, with peaks in total skunk rabies cases approximately 22 years apart. We examined public health casereports from 1960-2006 to identify trends, with the ultimate goal of developing a predictive model for skunk rabies epizootics. Cases were plotted by county, by year and certain trends were observed. Some counties regularly reported skunk rabies cases while many others reported no cases for several years. We also examined rainfall data from 4 representative counties to determine if there was a correlation between rainfall and skunk rabies cases. This paper presents the results of these investigations and presents opportunities for further investigations.